1993
DOI: 10.1143/jjap.32.l1365
|View full text |Cite
|
Sign up to set email alerts
|

Ingenious Method for Eliminating Effects of Heat Loss in Measurements of Thermal Diffusivity by ac Calorimetric Method

Abstract: Abslracl. A stmclure for ordered silicon-tin syslems on a silimn substrate, based on the known StNCtUre of a monolayer of tin on the (111) face of silicon, is propased. The corresponding electronic struclure of this syslem is modelled using the local densiy approximation to the densily functional theory of lhe electron gas in the KohnSham formulation wilh ab initio pseudopotentials taken tor lhe eleclron-ion interaction. The total energy is minimized including relaxation of all the ionic positions, and the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…(10) and (11), respectively. 22) In the case of spot heating, let us consider the experimental requirements for obtaining the true k in a similar way. The apparent decay constant, k a,app , derived from eq.…”
Section: Analysis Of Theoretical Resultsmentioning
confidence: 99%
“…(10) and (11), respectively. 22) In the case of spot heating, let us consider the experimental requirements for obtaining the true k in a similar way. The apparent decay constant, k a,app , derived from eq.…”
Section: Analysis Of Theoretical Resultsmentioning
confidence: 99%
“…In the distance-variation method, it has been proposed that we can obtain straightforwardly the true k from the correction of the heat loss by taking the geometrical average of the decay constant k a and phase shift k p as 25) k…”
Section: Ac Calorimetric Distance-variation Methodsmentioning
confidence: 99%
“…Gu et al [7] showed that the thermal diffusivity of the sample in this situation is given by the geometric mean of the two apparent thermal diffusivities, one obtained from the amplitude decay and the other from the phase shift, i.e.,…”
Section: Thermal Diffusivity Measurementmentioning
confidence: 99%